An expert system for site productivity improvement - Kaming, Peter Fortunatus; Ogunlana, Stephen O.; Worsalc Kanok-Nukulchai; Prapon Phasukyud; University of Atmajaya Yogyakarta (Bangkok : Asian Institute of Technology, 1992)
The past site productivity model has been reviewed, and a new model is introduced in this study. Based on the proposed model, an advisory expert system for improving site productivity has been created using the expert system shell EXSYS Multiple Criteria Weighting Technique, is adopted for developing the expert system. Knowledge bases is acquired from experts, textbooks, and current articles in journals. Knowledge representation uses IF - THEN - ELSE structure production system, and inference mechanism utilized backward chaining strategy. The expert system consists of four modules: Method and Technology, Site Management, Working Environment, and Motivation which can be run separately. Some issues regarding application of fuzzy set theory and multiple criteria weighting tech nique, multiple experts handling, validation expert system, and applying Analytical Hierarchical Process in rating the factors that affect site productivity were also examined. The current system need to be tested on site before it can be installed for daily use.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Expert systems (Computer science); Construction industry -- Management